Systematic Literature Review: Students' Mathematical Literacy Ability in Solving PISA Questions - Wulandari, Fitri; Meliasari, Meliasari; Flavilia Aurelia Hidajat (Westscience Press, 2025)
This study aims to review the literature related to students' mathematical literacy skills in solving PISA questions from gender and learning methods carried out from elementary school to tertiary education. This study uses the Systematic Literature Review (SLR) research method with research data found as many as 16 national and international articles published in the period 2018 – 2024. Data collection was carried out by documenting the relevant articles reviewed from the year of research, level of education, sample size in the study, and the type of research used. Based on the results of the study, it can be seen that articles on students' mathematical literacy skills in solving PISA questions have been reviewed from a learning method that has dominated in the last seven years. Meanwhile, research on students' mathematical literacy skills reviewed from a gender perspective still lacks interest in researchers. The majority of researchers conducted research at the junior high and high school education levels with a sample of less than 30. While the type of research that is often used is a qualitative research method with a descriptive approach.